Clinical and Neonatal Outcomes of Children Born After ICSI With or Without Surgically Acquired Sperm: A Retrospective Cohort Study - Du, Mingze; Zhang, Junwei; Li, Zhen; Liu, Yang; Wang, Kexin; Guan, Yichun (Frontiers in Endocrinology, 2022)
Objective: The purpose of this study was to explore the effects of different methods of obtaining sperm for intracytoplasmic sperm injection (ICSI) cycles on the live birth rate (LBR) and neonatal outcomes. Methods: This was a single-center retrospective cohort study conducted from January 2016 to December 2019. A total of 3557 ICSI cycles were included in the analysis, including 540 cycles in the surgically acquired sperm group and 3017 cycles in the ejaculated sperm group. The main outcome measure was the LBR. Results: The clinical pregnancy rate in the surgically acquired sperm group was 69.4%, which was significantly higher than the 59.7% clinical pregnancy rate in the ejaculated sperm group (P=0.01). The LBR of the surgically acquired sperm group was significantly higher than that of the ejaculated sperm group (63.1% vs. 51.2%, P<0.01). Similarly, the singleton LBR was also higher in the surgically acquired sperm group than in the ejaculated sperm group (45.4% vs. 39.2%, P=0.04). Due to differences in the baseline characteristics of the two groups, multiple logistic regression analysis was performed. After multiple logistic regression analysis, the different methods of obtaining sperm were independent risk factors influencing the clinical pregnancy rate (adjusted odds ratio (AOR)=0.73, 95% confidence (CI)=0.56-0.95, P=0.02) and LBR (AOR=0.69, 95% CI=0.54-0.89, P=0.01). The preterm birth rate (AOR=1.42, 95% CI=0.62-3.25, P=0.41) and the incidence of low birth weight (AOR=1.03, 95% CI=0.45-2.34, P=0.952), small for gestational age (AOR=0.81, 95% CI=0.39-1.68, P=0.57), macrosomia (AOR=0.88, 95% CI=0.47-1.66, P=0.70) and large for gestational age (AOR=1.08, 95% CI=0.65-1.82, P=0.76) were not affected by the different methods. Conclusion: The clinical pregnancy rate and LBR of the surgically acquired sperm group were higher than those of the ejaculated sperm group. There was no significant difference between the neonatal outcomes of the two groups.